Hypopituitarism Presenting as Heart Failure-A Case Series - Ahmad, Imran; Siddiqui, Abdul Hameed; Siddiqui, Ahreema (Pakistan Armed Forces Medical Journal, 2025)
Hypopituitarism, an uncommon endocrine disorder, presents a diagnostic challenge due to its variable and often vague manifestations. It can have severe, life-threatening complications including heart failure. In this case series, we reported five cases with hypopituitarism presented as heart failure, each exhibited unique etiologies and presentations. Out of these, two cases were associated with Sheehan’s syndrome, two with Empty Sella Syndrome, and one with isolated ACTH deficiency. Clinical evaluation, hormonal assays, and imaging studies were instrumental in confirming diagnoses. Hormone replacement therapy led to symptomatic and functional cardiac recovery in these patients, highlighting the importance of considering hypopituitarism in cases of unexplained heart failure. This series emphasizes early recognition and appropriate treatment of hypopituitarism to prevent significant morbidity and mortality.